Matching study areas using Google Street View: A new application for an emerging technology. (December 2015) - Less, Elyse Levine; McKee, Patricia; Toomey, Traci; Nelson, Toben; Erickson, Darin; Xiong, Serena; Jones-Webb, Rhonda
Highlights: A GSV-based neighborhood audit is proposed to measure and match study areas. Reliability and utility are assessed. GSV-based audits can be used for measuring and matching study areas. Abstract: Google Street View (GSV) can be used as an effective tool to conduct virtual neighborhood audits. We expand on this research by exploring the utility of a GSV-based neighborhood audit to measure and match target and comparison study areas. We developed a GSV-based inventory to measure characteristics of retail alcohol stores and their surrounding neighborhoods. We assessed its reliability and assessed the utility of GSV-based audits for matching target and comparison study areas. We found that GSV-based neighborhood audits can be a useful, reliable, and cost-effective tool for matching target and comparison study areas when archival data are insufficient and primary data collection is prohibitive. We suggest that researchers focus on characteristics that are easily visible on GSV and are relatively stable over time when creating future GSV-based measuring and matching tools. Dividing the study area into small segments may also provide more accurate measurements and more precise matching.